Alton's Paradox Foreign Film Workers and the Emergence of Industrial Cinema in Latin America. - Poppe, Nicolas (SUNY Press, 2021)
Uses extensive archival research to explore the manifold contributions of foreign film workers to emerging film industries in Latin America from the 1930s to early 1940s.
Keywords: Motion picture industry -- Latin America -- History -- 20th century.; Foreign workers -- Latin America -- History -- 20th century.; Cinéma -- Industrie -- Amérique latine -- Histoire -- 20e siècle.; Travailleurs étrangers -- Amérique latine -- Histoire -- 20e siècle.; Foreign workers; Motion picture industry; Latin America; ART / Film & Video; 1900-1999; History